Human IL-32θA94V mutant attenuates monocyte-endothelial adhesion by suppressing the expression of ICAM-1 and VCAM-1 via binding to cell surface receptor integrin αVβ3 and αVβ6 in TNF-α-stimulated HUVECs - Park, Jae-Young; Park, Hyo-Min; Kim, Seonhwa; Jeon, Kyeong-Bae; Lim, Chae-Min; Hong, Jin Tae; Yoon, Do-Young (Frontiers in Immunology, 2023)
Interleukin-32 (IL-32), first reported in 2005, and its isoforms have been the subject of numerous studies investigating their functions in virus infection, cancer, and inflammation. IL-32θ, one of the IL-32 isoforms, has been shown to modulate cancer development and inflammatory responses. A recent study identified an IL-32θ mutant with a cytosine to thymine replacement at position 281 in breast cancer tissues. It means that alanine was also replaced to valine at position 94 in amino acid sequence (A94V). In this study, we investigated the cell surface receptors of IL-32θA94V and evaluated their effect on human umbilical vein endothelial cells (HUVECs). Recombinant human IL-32θA94V was expressed, isolated, and purified using Ni-NTA and IL-32 mAb (KU32-52)-coupled agarose columns. We observed that IL-32θA94V could bind to the integrins αVβ3 and αVβ6, suggesting that integrins act as cell surface receptors for IL-32θA94V. IL-32θA94V significantly attenuated monocyte-endothelial adhesion by inhibiting the expression of intracellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) in tumor necrosis factor (TNF)-α-stimulated HUVECs. IL-32θA94V also reduced the TNF-α-induced phosphorylation of protein kinase B (AKT) and c-jun N-terminal kinases (JNK) by inhibiting phosphorylation of focal adhesion kinase (FAK). Additionally, IL-32θA94V regulated the nuclear translocation of nuclear factor kappa B (NF-κB) and activator protein 1 (AP-1), which are involved in ICAM-1 and VCAM-1 expression. Monocyte-endothelial adhesion mediated by ICAM-1 and VCAM-1 is an important early step in atherosclerosis, which is a major cause of cardiovascular disease. Our findings suggest that IL-32θA94V binds to the cell surface receptors, integrins αVβ3 and αVβ6, and attenuates monocyte-endothelial adhesion by suppressing the expression of ICAM-1 and VCAM-1 in TNF-α-stimulated HUVECs. These results demonstrate that IL-32θA94V can act as an anti-inflammatory cytokine in a chronic inflammatory disease such as atherosclerosis.